Perspectivas para triagem Genética da intolerância à lactose: rastreamento do polimorfismo -13910 C/T, no gene MCM6, em neonatos - Arroyo, Marta Alves da Silva (2010)
Lactose intolerance has been, for many years, considered as a worldwide problem in many children and adults. Objective: The aim is to investigate the prevalence of polymorphism -13910C/T, in a neonatal tracking, for early diagnosis of lactose tolerance/intolerance. Material and Methods: A cross-sectional case study of 310 Brazilian newborns. DNA was extracted from leukocyte umbilical cord and specific primers were used to amplify the region that encloses the -13910C/T polymorphism of the MCM6 gene, using the polymerase chain reaction and the restriction fragment length polymorphism tests. Results: One hundred and sixty (52%) male newborns and 150 (48%) female were evaluated. From these, 191 (62%) presented CC genotype (lactose intolerant), 95 (31%) CT genotype, and 24 (7%) TT genotype, comprising a total of 119 (38%) lactose tolerant newborns. According the newborns´ gender distribution in relation to the phenotypes has been found 97 (32%) of male gender and 94 (30%) of female gender lactose intolerant, and 63 (20%) male and 56 (18%) female lactose tolerant newborns, not being such distribution statistically significant (p = 0.801). Conclusions: The molecular analysis made possible the identification of the presence or absence of lactase persistence variant in Brazilian newborns. The neonatal molecular diagnosis can optimize the follow-up of positive results in newborn screening for lactose intolerance.